Croatian post-socialist transition or transformation : lost in translation - Jambrač, Josip (Array, 2020)
The article analyses some constitutional changes and social phenomena over thirty years of transition and transformation of the economy and society in Croatia. The findings point at very frequent radical changes in key institutions and the tendency to believe that problems can be solved via formal legislative approach. Most of Croatia’s main problems (political and societal) arise from the wrong choice and performance of democratic and market institutions and understanding of integrations. The adopted legislation has not provided for predictability, Preliability, or system stability in key areas of human interaction. The findings indicate an ambivalent attitude of the actors towards the state, the political system, and the rule of law. After three decades of transition and transformation, the failure of the established model of political governance is visible. In order tochange the model of political governance, there must be an agreement about the political role model and the consensus about the fundamental values of society.